Pengaruh Mutasi, Reward, dan Promosi Jabatan terhadap Prestasi Kerja - Adhari, Aryushi; Ruswidiono, R Wasisto (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
The purpose of this study is to analyze and determine the influence of mutation, reward, and promotion on the job performance of employees at CV Yoehan Busana. The research design used in this study is descriptive and causal research. The population in this study is all employees of CV Yoehan Busana. The sample used in this study consists of 153 employees from all divisions, selected using saturated sampling technique. The data collection technique used in this study is a questionnaire. The method for analysis in this study is multiple linear regression. The results of this study indicate that mutation does not have an effect on the job performance of employees at CV Yoehan Busana, while reward and promotion have an effect on the job performance of employees at CV Yoehan Busana. This is because mutation is seen as a punishment, while reward and promotion are seen as an appreciation of employee performance.